2022
DOI: 10.1093/jxb/erac406
|View full text |Cite
|
Sign up to set email alerts
|

RsCLE22a regulates taproot growth through an auxin signaling-related pathway in radish (Raphanus sativus L.)

Abstract: CLAVATA3/EMBRYO SURROUNDING REGION-related (CLE) peptides are a class of small polypeptide molecules involved in plant growth and development. Although radish is an important root vegetable crop worldwide, the functions of CLE peptides in taproot formation remain elusive. Here, a total of 48 RsCLE genes were identified from the radish genome. RNA in situ hybridization showed that RsCLE22a gene was highly expressed in the vascular cambium. Overexpression of RsCLE22a inhibited root growth by impairing stem cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…The SWEET17 gene is mainly expressed in vascular tissue and meristem cells of the root tip, which is involved in lateral root development in Arabidopsis plants [23]. The cambium mediates the process of root thickening, which strongly plays an essential role in the yield of root crops [40,58]. In the current study, RsSWEET17 was found to be highly abundant in roots and specifically expressed in the cambium regions of the radish taproot.…”
Section: Rssweet17 Positively Regulates Sugar Accumulation and Root G...mentioning
confidence: 50%
“…The SWEET17 gene is mainly expressed in vascular tissue and meristem cells of the root tip, which is involved in lateral root development in Arabidopsis plants [23]. The cambium mediates the process of root thickening, which strongly plays an essential role in the yield of root crops [40,58]. In the current study, RsSWEET17 was found to be highly abundant in roots and specifically expressed in the cambium regions of the radish taproot.…”
Section: Rssweet17 Positively Regulates Sugar Accumulation and Root G...mentioning
confidence: 50%
“…Due to the interaction between RALF and FER under salt stress, we speculate that RALF may also have intricate connections with plant hormones, akin to other plant peptides [112]. Recent findings indicate that ethylene downregulates the expression of CsRALF34 in cucumber [71], whereas in Arabidopsis, AtRALF34 is modulated by both auxin and ethylene [59]. Furthermore, the external application of SpPIP1 modulates jasmonic acid levels, thereby enhancing tomato resistance to stress [113].…”
Section: Plant Peptides Control the Biosynthesis Of Hormonesmentioning
confidence: 97%
“…The antimicrobial peptide DmAMP1W from wheat curtails the proliferation of fungi, including fungi Rhizoctonia cerealis and Bipolaris sorokiniana, effectively combating wheat sharp eyespot and root rot diseases [70]. Additionally, a variety of small peptides, such as those released by papain-like cysteine proteases, Defensin-Derived Antifungal Peptides, and small cysteine-rich (SCR) secreted proteins like RsMf8HN, play an integral role in plants' defense against fungal and bacterial pathogens [71][72][73]. The peptide VISP1, acting as a selective autophagy receptor, plays an essential role in plant immunity [74].…”
Section: Other Functions Of Small Peptides In Plant Growth and Develo...mentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of genes have been identified to involve in the process of rhizome development. For instance, radish CycD3 and RsCLE22a gene were confirmed to participate in the formation of fleshy roots ( Lutova et al., 2008 ; Dong et al., 2022 ). Two MADS-box genes could regulate vascular cambium activity and secondary growth of poplar by regulating IAA homeostasis ( Zheng et al., 2020 ).…”
mentioning
confidence: 99%